2017
DOI: 10.22214/ijraset.2017.11037
|View full text |Cite
|
Sign up to set email alerts
|

Saffron Crop (Golden Crop) in Modern Sustainable Agricultural Systems

Abstract: Saffron (Crocus sativus L.) is an autumnal flowering plant valued for dried stigmas are well known for their aromatic and colouring power. It possesses a number of medicinally important activities and helpful in controlling various diseases. Saffron has a reverse biological cycle compared with the majority of cultivated plants: flowering first in October-November, then vegetative development until May, which means that the vegetative development is not directly important for the production of stigmas, but for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The corms tend to rot in humid or water-logged soils (Sampathu et al, 1984). It can be well grown from well drained clay soil and loose clay calcareous soils to sandy or loamy textured soils with slightly saline conditions (Dar et al, 2017;Mashayekhi and Latifi, 1998;Menia et al, 2018;Shahandeh, 2020). A group researchers reported that the yield was highest in the sandy soil while soil water supply, nutrient uptake, and safranal content were higher in clay soil (Husaini et al, 2010).…”
Section: Soil Requirementmentioning
confidence: 99%
See 1 more Smart Citation
“…The corms tend to rot in humid or water-logged soils (Sampathu et al, 1984). It can be well grown from well drained clay soil and loose clay calcareous soils to sandy or loamy textured soils with slightly saline conditions (Dar et al, 2017;Mashayekhi and Latifi, 1998;Menia et al, 2018;Shahandeh, 2020). A group researchers reported that the yield was highest in the sandy soil while soil water supply, nutrient uptake, and safranal content were higher in clay soil (Husaini et al, 2010).…”
Section: Soil Requirementmentioning
confidence: 99%
“…Weed control is necessary for a crop's healthy growth. Weeds can also be managed with the herbicides Simazine or Atrazine at 1.0 kg ha −1 (Dar et al, 2017;Pandy and Srivastava, 1979).…”
Section: Weed Managementmentioning
confidence: 99%
“…), saffron was used as a condiment. [5] The first evidence of saffron cultivation is of a much later date and can be traced to the Minoan civilization of 1550 years B. C., as inscribed in the Papyrus Eber. [6] This Egyptian medical document referred to the frescoes in the Palace of Knossos, which portrayed young girls picking saffron flowers while holding baskets.…”
Section: The Origin Of Saffronmentioning
confidence: 99%
“…Saffron has long been considered a minor crop used merely for the needs of agricultural diversification. In recent years, saffron has acquired a more interesting role in low-input farming systems (no use of fertilizers and chemical treatments, low irrigation water requirement), becoming a viable alternative for sustainable agriculture (Mollafilabi et al, 2021;Dar et al, 2017;Sahabi et al, 2016;Gresta et al, 2008). Indeed, given its morphology and physiology, saffron is a rustic crop able to cope with severe weather conditions (Alizadeh et al, 2009;Molina et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The high labor requirements, concentrated over a few days and a few hours per day, and growing costs have led to a reclassification of saffron-producing countries (Giupponi et al, 2019;Dar et al, 2017;Gresta et al, 2008). In European countries, the traditional producers (Spain, Italy and Greece), have seen a decline in their production areas despite the increase in saffron prices (Dar et al, 2017;Gresta et al, 2008;Fernández, 2004). By contrast, a strong increase in saffron production has been recorded in Iran and other Asian countries, where labor is still cheap in comparison (Mzabri et al, 2021;Yasmin et al, 2018;Gresta et al, 2008).…”
Section: Introductionmentioning
confidence: 99%